Differential biofilm formation and chemical disinfection resistance of Escherichia coli on stainless steel and polystyrene tissue culture plate - Muazu, Anas; Rahman, Nor Iza A.; Aliyu, Sani; Abdullahi, Umar Faruk; Umar, Ahmed Faruk; Ogidi, Jonathan Ajisafe (International Journal of Research in Medical Sciences, 2017)
Background: Biofilms are aggregates of microbial cells enclosed in an extracellular polymeric substance and attached to surfaces. Biofilm formation and its resistance to antimicrobials is becoming a serious challenge in food industries and hospital settings. The aim of this work was to study the formation of biofilm by E. coli on Stainless steel (SS) and Polystyrene Tissue Culture Plate (TCP) at 10 and 27°C, and also to assess the action Hydrogen Peroxide (HP), Para Acetic Acid (PAA), Sodium Hypochlorite (SH) and mixture of PAA + SH disinfectants against the biofilm. Methods: 200 µL of 108 suspension of E. coli ATCC 29922 was inoculated on the SS and into the wells of TCP, incubated at 10 and 27°C for 24, 48 72 and 168 hours. Biofilm developed at each incubation hour above was quantified by bead-vortex method followed by agar plating. The action of disinfectants was tested on 168 hours biofilm. The surfaces were exposed to the disinfectants and incubated at 27°C for 10 minutes, followed by deactivation for 5 minutes. Cells that resisted disinfectants action were vortexed and enumerated by agar plating. Results: From the results E. coli developed higher biofilm on SS than TCP at 72 hours and 27°C. After disinfection, HP was the most effective with log reduction value of 1.11 followed by PAA (1.07), then PAA + SH (1.04) while SH was the least (0.92). Conclusions: The result of this work showed that HP and PAA can be good disinfectants against E. coli biofilm.